2018
DOI: 10.1112/blms.12227
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Galois groups of trinomials and Odoni's conjecture

Abstract: We prove that for every prime p, there exists a degree p polynomial whose arboreal Galois representation is surjective, that is, whose iterates have Galois groups over Q that are as large as possible subject to a natural constraint coming from iteration. This resolves in the case of prime degree a conjecture of Odoni from 1985. We also show that a standard height uniformity conjecture in arithmetic geometry implies the existence of such a polynomial in many degrees d which are not prime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Looper [153] recently proved Odoni's conjecture (Conjecture 5.4) for K = Q and all prime degrees d, and a number of researchers [23,130,220] independently extended Looper's work. In particular, Specter [220] proved Odoni's conjecture for all number fields, and more generally, for all algebraic extensions K/Q that are unramified outside of a finite set of primes.…”
Section: Arboreal Representationsmentioning
confidence: 99%
“…Looper [153] recently proved Odoni's conjecture (Conjecture 5.4) for K = Q and all prime degrees d, and a number of researchers [23,130,220] independently extended Looper's work. In particular, Specter [220] proved Odoni's conjecture for all number fields, and more generally, for all algebraic extensions K/Q that are unramified outside of a finite set of primes.…”
Section: Arboreal Representationsmentioning
confidence: 99%
“…Taking the inverse limit φ = lim ←− φ n , one obtains a homeomorphism (34), which satisfies (35) for all u ∈ P d and all g ∈ Φ(G) since every φ n has property (39). This extends to the condition (35) on the closures of Φ(G) and H.…”
Section: Asymptotic Discriminant For Arboreal Representationsmentioning
confidence: 95%
“…Since then, a flurry of results for polynomials of degree d=2 have been obtained, we refer to Jones for an overview. Examples of polynomials satisfying the Odoni conjecture in all prime degrees d3 for K=Q were obtained by Looper . Juul studied this question for rational functions over fields of positive characteristic.…”
Section: Introductionmentioning
confidence: 99%
“…If d = 2, then f is of the form of Theorem 3.2, and the relations (8) show that f satisfies condition (i) of Theorem 3.1. Similarly, if d 4, then f is of the form of Theorem 3.1, and relations (8) show that f satisfies conditions (i) and (ii) of that Theorem. In both cases, we claim that for each n 1, the quantity F n of equation (4) is not a square modulo p = p 2 .…”
Section: Proof Of Odoni's Conjecture For D Evenmentioning
confidence: 98%
“…Stoll [13] produced infinitely many such polynomials for F = Q and d = 2. In 2016, Looper showed that Odoni's conjecture holds for F = Q and d = p a prime [8].…”
Section: Introductionmentioning
confidence: 99%